Complete Gauge theory for the whole Poincaré group - Aldrovandi, R.; Stédile, E. (Springer Nature, 1984)
Gauge theories for nonsemisimple groups are examined. A theory for the Poincaré group with all the essential characteristics of a Yang-Mills theory necessarily possesses extra equations. Inonü-Wigner contractions of gauge theories are introduced which provide a Lagrangian formalism, equivalent to a Lagrangian de Sitter theory supplemented by weak constraints. © 1984 Plenum Publishing Corporation.